2016
DOI: 10.1177/0895904815625286
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting Early Career Trajectories

Abstract: Career decisions of four teachers are explored through the concept of figured worlds in this qualitative, longitudinal case study. Participants were purposefully chosen for similarity at entry, with a range of career trajectories over time. Teacher career paths included remaining in one school, repeated changes in schools, attrition after relocation, and nonrenewal of contract. Data included interviews, observations, participants' assessments, and pupils' work. Cross-case analysis suggests that no single teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 70 publications
0
12
0
3
Order By: Relevance
“…While average statistical findings can be useful for generalization purposes, it is important, to acknowledge that the individual needs of teachers are often not homogenous. For example, Barnatt et al (2017) longitudinally examined how the career trajectories for beginning teachers with similar backgrounds resulted in different outcomes. Results from their qualitative analysis suggest that no single factor or policy thoroughly explains the variation in teaching career outcomes for their sample, but rather their careers are affected by teachers’ sense-making of how they fit into the teaching world and the interaction between that world and themselves.…”
Section: Employment Solutions In Hard-to-staff Contextsmentioning
confidence: 99%
“…While average statistical findings can be useful for generalization purposes, it is important, to acknowledge that the individual needs of teachers are often not homogenous. For example, Barnatt et al (2017) longitudinally examined how the career trajectories for beginning teachers with similar backgrounds resulted in different outcomes. Results from their qualitative analysis suggest that no single factor or policy thoroughly explains the variation in teaching career outcomes for their sample, but rather their careers are affected by teachers’ sense-making of how they fit into the teaching world and the interaction between that world and themselves.…”
Section: Employment Solutions In Hard-to-staff Contextsmentioning
confidence: 99%
“…It is also considered reasonable that the education managers take anticipatory steps to prepare the skills to survive in this era. The change of the society's views should be accommodated by the committees of the educational institutions, so that the services offered to the society can be accepted (Barnatt et al 2017;Díaz-Gibson, Zaragoza, Daly, Mayayo & Romaní 2017;Nguyen 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Despite Don's reports of feeling inadequate, he provided examples of how he felt he was attempting to support student learning and he spoke of remaining optimistic that he would better understand how to successfully incorporate literacy practices into his teaching. Barnatt et al (2016) noted "the interplay between a teacher's identity and agency was key" (p. 25). This interplay appeared to shape Don's teacher identity.…”
Section: Don's Teacher Identitymentioning
confidence: 99%
“…Barnatt et al (2016) identified two sets of factors in their review of the literature regarding ECTs' decision-making: "[1] those involving teachers' expectations about teaching practice and their subsequent sense of efficacy and emotional well-being…and [2] those that allow novice teacher to exhibit agency and… [to] persevere" (p. 9). Barnatt et al (2016) found the ECTs in their study all encountered "disequilibrium" (p. 25) in their school contexts, and that the varying degrees of sense of agency each teacher felt were critical to the response each made. In other words, "the interplay between a teacher's identity and agency was key" (p. 25).…”
Section: Ects' Development Of Teaching Practicesmentioning
confidence: 99%